Strategi Dinas Tenaga Kerja Dalam Penanggulangan Angka Pengangguran Di Kota Ambon - Haikutty, Frensya; Madubun, Jusuf; Tuhumury, Joana Joanita (Journal of Government Science Studies, 2024)
Strategies of the Department of Manpower in Mitigating Unemployment in Ambon City. This study is a descriptive qualitative research aimed at understanding the strategies of the Department of Manpower in mitigating unemployment. The research was conducted at the office of the Department of Manpower in Ambon City, Maluku Province. The data sources included both primary and secondary data. Data collection techniques involved interviews, observations, and documentation. Data analysis techniques were carried out in three stages: data reduction, data presentation, and conclusion drawing. The results of this study indicate that the main challenges in evaluating and formulating policies to mitigate unemployment in Ambon City, particularly in the programs conducted by the Department of Manpower, are primarily due to data limitations. These limitations pose significant obstacles to effective evaluation and policymaking. The need for improved data infrastructure and collaboration with related institutions is proposed as a solution. This research provides crucial insights for stakeholders in efforts to mitigate unemployment in Ambon City.